How to assess the quality and transparency of energy scenarios: Results of a case study. (November 2019) - Junne, Tobias; Xiao, Mengzhu; Xu, Lei; Wang, Zongfei; Jochem, Patrick; Pregger, Thomas
Abstract: The exploration and evaluation of strategies for decarbonizing the energy system is the subject of a series of national and international studies conducted by governmental, industrial and independent stakeholders. These studies play an important role in the energy policy debate on understanding and assessing different transformation paths of the energy system, technology options and their implications. They support strategic decisions on the type and scale of investments in the energy system under uncertain future conditions. However, in recent years the increasing complexity of these studies lead to a decreasing transparency even though their transparency and traceability is important for society, politics, research, and industry. In this article, three energy scenarios at different regional scales are reviewed according to their compliance with our pre-defined criteria of transparency. They are analysed in detail with regard to their objectives, methods, data used, results obtained and traceability. Our comparison shows that the results are often presented sufficiently in order to inform decision makers. However, the underlying model-based methods lack information on data exchange between the models, the transparent description of model couplings and a discussion on the rationality of method selection and the strengths and weaknesses of the applied approaches. Based on our findings, we present some general advice for energy scenario developers on how to ensure transparency and traceability in future energy scenario studies. Highlights: Scenario studies lack information on data exchange between the models. A transparent description of model couplings is often missing. An in depth discussion on the rationality of method selection is needed. Demands from open data and source code initiatives should become standard.